P13 DIFFERENCE IN LONG-TERM QUALITY OF LIFE BETWEEN MCKEOWN AND IVOR LEWIS ESOPHAGECTOMY. (23rd November 2019) - Jezerskyte, E; Saadeh, L M; Hagens, E R C; Sprangers, M A G; Noteboom, L; van Laarhoven, H W M; Eshuis, W J; van Berge Henegouwen, M I; Gisbertz, S S
Abstract: Aim: The purpose of this study was to investigate the difference in long-term health-related quality of life (HR-QoL) between McKeown and Ivor Lewis esophagectomy in a tertiary referral center. Background & Methods: The therapy of esophageal cancers consist of (neo)adjuvant chemo(radio)therapy and surgery. Often different surgical approaches are possible such as transthoracic esophagectomy with a cervical anastomosis (McKeown) or an intrathoracic anastomosis (Ivor Lewis). Evidence is scarce on whether either of these approaches is better in terms of survival, perioperative morbidity, pathology results and quality of life. Patients with mid-, distal esophageal, gastroesophageal (GEJ) or cardia carcinoma who have undergone a McKeown or an Ivor lewis esophagectomy in the period of 2003 – 2018 were included in this study. EORTC QLQ-C30 and EORTC QLQ-OG25 questionnaires were handed out during the outpatient clinic visits and a follow-up of at least one year was ensured. Problems with eating, reflux and nausea and vomiting were chosen as primary HR-QoL domain endpoints while the remaining HR-QoL domains, postoperative complications and pathology results were observed as secondary endpoints. Correction for confounders age and gender was performed. Results: 147 patients were included in the McKeown group and 120 in the Ivor Lewis group. Mean age was 63.5 years and median follow-up was three years (range 12-137 months). No significant difference was found in problems with eating, reflux and nausea and vomiting. Significantly more problems with eating with others were found in McKeown group (β=10.435, 95% CI 4.474 – 16.395) and anastomotic leakage was significantly more common after McKeown esophagectomy (p=0.004). No significant difference was found in Clavien Dindo classification. During Ivor Lewis esophagectomy significantly more lymph nodes were resected (p<0.001). Number of lymph node metastases and R0 resection rate did not differ between groups. Conclusion: No major differences in long-term HR-QoL were found in patients with mid-, distal esophageal, GEJ or cardia carcinoma following McKeown or Ivor Lewis esophagectomy. Problems with eating with others and anastomotic leakages were more common after McKeown esophagectomy, however, Clavien Dindo classification and radicality of surgery were similar between the two groups. Results of this study could assist the patient during the decision-making process prior to the surgery.